Historical Novel in Turkish Literature: The Novel “Shah and Sultan” by Iskender Pala - Safina, Elmira S.; Shafigullina, Lilia S. (Journal of History Culture and Art Research, 2017)
The purpose of the article is to reveal the formation and the development of historical novel genre in Turkish literature and to reveal some of its characteristic features using the example of the novel "Shah and Sultan" by the Turkish writer Iskender Pala. In this study we relied on comparative and descriptive methods of the study. We also used the method of historical analysis. Iskender Pala's novel "The Shah and the Sultan" is defined by the author of this study as a true historical novel based on genuine historical figures and events. The practical significance of the work is related to the fact that the materials and the results of this study can be used in the course of lectures on contemporary Turkish literature, as an example during literature seminars, and also to continue the study of the writer's work as a whole. Thus, we see that the genre of the novel, in particular historical one, is a relatively new phenomenon in Turkish literature. The novel by Iskandar Pala "Shah and the Sultan" is a prime example of the modern Turkish historical novel, which was based on genuine historical figures and events.